Evaluation of the Womens Health Services Physical Activity Project to Encourage Women and Their Families to Become More Active - McManus, Alexandra; Nicholson, Claire; Lee, S. (Centre of Excellence Science Seafood & Health, Curtin Health Innovation Research Institute (CHIRI), 2010)
In 2008 the Womens Health Services in Northbridge, Western Australia, was the recipient of a Healthy Active Australia grant, funded by the Commonwealth Department of Health and Ageing. The aim of the funded project was to increase participation and physical activity levels of marginalised women by introducing them to a range of low cost, easily accessible exercise opportunities and by providing relevant health information. The program ran from late 2008 to early 2010. Program activities included the delivery of thirty three health information talks covering topics such as nutrition, healthy eating,relaxation, stress and the need for adequate levels of vitamin D, as well as forty two blocks of physical activity classes. Activities included swimming, yoga, pilates, gentle exercise and dancing. Other physical activities included three Come and Try days, four organised walks and six bike workshops.Five family activity sessions were also held over the funding period. A qualitative evaluation of the activities was conducted by Curtin University. Evaluation activities included eight focus groups with approximately sixty participants, eight one-on-one interviews with participants and fourinterviews with class instructors. Overall, participants were satisfied with the physical activity program they were participating in. Participants reported that the program had increased their levels of activity, in many cases by providing an opportunity to be active that they would not otherwise have. Barriers to engaging in physical activity included financial barriers such as a lack of money to pay for services andchildcare, a lack of affordable services and a lack of culturally appropriate facilities. Other barriersincluded personal factors such as a lack of confidence or a lack of motivation.Many women, especially those caring for children, did not have time to engage in physical activity outside of their sessions with the WHS. For these women, the sessions offered them 'time out' from the pressures of their everyday lives. Other women experienced mental health issues which affected their ability to engage in physical activity. In addition to providing women with the opportunity to be active, participants also reported experiencing physical and mental health benefits as a result of the program. The program gave participants the opportunity to mix with peers in a nonjudgmental environment, introduced them to new activities and provided the opportunity to learn new skills. This report presents the findings of an independent qualitative evaluation of participants' experiences with the program.